THE RESPONSES OF THE NON-ENGLISH DEPARTMENT STUDENTS TOWARD ENGLISH AS AN OBLIGATORY SUBJECT - Murnia Suri (Universitas Ubudiyah Indonesia, 2018)
This study aims to know how the students of non-English Department students of Ubudiyah University (UUI) respond to English subject. The study measurement focuses on students’ responses toward teaching learning process in the English class. The sample of this study was non-English department students of UUI from the students from the Technical Information department. The students were the second-year students who studied in UUI and were obligated to take the English class as one of the public subjects. The method used in this research were oral test and questionnaire. The oral test done by asking questions about students’ daily activity, elaborating a trending topic and inviting students to discuss about up to date news. The method used to collect the data from questionnaire was by distributing a closed questionnaire to the students about how their feeling to English. From the data obtained from the oral test, it was found the students seemed enthusiast in the beginning of teaching learning process, it was observed the students’ curiosity about English and how the students’ responses to the teacher’s explanation the female students had highercuriosity than male students and it also found the students who took a frontage row in sitting were deeply interested for English lesson compared to those who were in the rare position. When the oral test held the students seemed easily answered the questions about daily activity but then when they were asked the idea about a trending topic and an up to date news, they faced some obstacles. The obstacles of this problem were answered in the questionnaire sheets then. The students’ showed slow responses toward the questions, sharing and explanation when the oral test conducted because they were lack of English vocabulary, poor pronunciation and confusing in grammatical mastery.Keywords: responses, non-English department students, obligatory subject